Edukasi Dampak Nikah Siri terhadap Perlindungan Hukum Perempuan dan Anak di Masyarakat Pedesaan - Roidatus Shofiyah; M. Sifa Fauzi Yulianis; Atmari Atmari; Mirza Elmy Safira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The practice of unregistered marriage (marital unregistered marriage) remains widespread in rural communities and raises various legal issues, particularly those related to the protection of women and children. Low public understanding of the importance of marriage registration is a major factor driving this practice. This community service activity aims to increase public legal awareness about the impacts of unregistered marriage. The method used was a participatory approach through outreach, interactive discussions, and assessment of understanding using pre- and post-tests in Soket Dajah Village, Tragah District, Bangkalan Regency, Madura. The results of the activity indicate an increase in public understanding of the importance of marriage registration as a form of legal protection for women and children. Furthermore, participants began to understand the legal consequences that can arise from the practice of unregistered marriage. This activity contributed to raising public legal awareness and opened up opportunities for ongoing legal education at the village level.